IMPLEMENTATION PROGRAME EVALUATION OF SOCIAL HEALTH SERVICE IN HEALTH INSURANCE BY FAMILY DOCTOR IN PONTIANAK - Imran, Imran (IJHCM (International Journal of Human Capital Management), 2018)
The purpose of the research was to evaluate the implementation of health service process, participant of social health insurance by family doctor, that consist of necessary, the background of the program, readiness of the program, realization of the program and the accomplishment of the health service program in health insurance by family doctor. The research used qualitative and quantitative approach by CIPP (Context, Input, Process, Product) evaluation model. The participants of social health insurance program by family doctor were 10.487 people. Most of them gave positive response and the satisfaction index of health service by family doctor was good. The result of the research showed the implementation of health service in health insurance by family doctor have done with the appropriate purpose and standard. The result of this evaluation research was the health service in health insurance program by family doctor could increase the participants of health insurance’s health level in Pontianak City and it can be continued by The Social Health Insurance Provider. Keywords: Social health insurance, family doctor, health service program, health level.